Pengaruh Pertumbuhan Perusahaan, Kebijakan Dividen, Dan Likuiditas Terhadap Nilai Perusahaan Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2021 - Made Arya Dyasti Pertiwi; Kadek Dewi Padnyawati; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2023)
A company needs sufficient capital to remain competitive and continue to operate. Funds required by the company are usually raised by investors. Improving corporate value can encourage investors to invest. Purpose of studys is to determines the impact of corporate growth, dividend policy and liquidity on the value of companies in the banking sector listed on the BEI for period 2017-2021. All banking companies included in this study were listed on the BEI from 2017 to 2021, for total 47 companies. A targeted sampling technique is used to obtain sample 10 banking sector companies listed on the BEI to determine the sample in this study. These results show that the higher the bank's dividend policy and liquidity, the higher the company's value. Growth rate will have a positive impact, but it will be less significant, hence his the first hypothesis is rejected. It is recommended to use different independent variables for different results.